A revision of Agaricus section Arvenses with nine new species from China. (2nd January 2021) - Cao, Bin; He, Mao-Qiang; Ling, Zhi-Lin; Zhang, Ming-Zhe; Wei, Sheng-Long; Zhao, Rui-Lin
ABSTRACT: Agaricus sect. Arvenses includes numerous species that are potential candidates for cultivation, and some have high nutritional and medicinal interests. Between 2012 and 2017, 147 specimens of A . sect. Arvenses were collected in China. For this study, nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2 (ITS), nuc 28S rDNA (28S), and translation elongation factor 1-alpha ( tef1 ) sequences were used to assess species boundaries of these samples from China. Combined with morphological examination, we recognize 22 species of A . sect. Arvenses from China, of which 12 are known species, one is new record for China, and nine are proposed as new.